The Efficiency Of Landfill Leachate Treatment By Adsorption Process With Biochar - Idris, Nurul Najihah Mohd (Universiti Sains Malaysia, 2022)
Landfill leachate contains large amount of organic and inorganic contaminants. The organic and inorganic pollutants are hazardous and bring negative impact towards the environment. The landfill leachate must be handled in order to prevent contamination of these hazardous compositions generated by the leaching process. The chemical-physical adsorption process is the recommended treatment that has been discussed in this research. The adsorption of activated carbon (AC) is one of the best methods to treat stabilised landfill leachate. This method, however, needed expensive and limited AC precursor components. The goal of this research is to identify alternative adsorbents that could effectively lower the contaminants in landfill leachate but are less expensive. Biochar was used as an activated carbon media in this study. The removal efficiency of COD, turbidity and zinc in the landfill leachate was assessed by biochar adsorbent. Adsorbent dose and pH are the two parameters that are the focus of the approach for laboratory research The optimum dosage of biochar achieved throughout this research was 1g for removal COD, 2g for removal turbidity, 2.5g for removal zinc and 3g for removal suspended solids. The optimum pH achieved was pH 4 for removal COD, zinc and suspended solid. As for the removal of turbidity, the ideal pH was pH 12. The optimal pH for zeta potential to near the zero point charge is pH 4 and the particle size is smallest at pH 12. Overall, the biochar that been used was efficient to reduce COD and Zinc.